Genetically engineered biological agents in therapy for systemic lupus erythematosus - Elena Aleksandrovna Aseeva; S K Solovyev; E L Nasonov (Современная ревматология, 2013)
Systemic lupus erythematosus (SLE) is a prototype for chronic autoimmune disease. Its prevalence is 20 to 70 cases per 100,000 women and varies by race and ethnicity. Despite considerable progress in traditional therapy, many problems associated with the management of these patients need to be immediately solved: thus, 50-80% are found to have activity signs and/or frequent exacerbations and about 30% of the patients have to stop work; Class IV lupus nephritis increases the risk of terminalrenal failure. In the past 20 years great progress has been made in studying the pathogenesis of SLE: biological targets to affect drugs have been sought and fundamentally new therapeutic goals defined. Belimumab is the first genetically biological agent specially designed to treat SLE, which is rightly regarded as one of the most important achievements of rheumatology in the past 50 years.